(untitled) (Estudos críticos em organização do conhecimento, 2024)
this chapter deals with historiographical and critical approaches to knowledgeorganization systems, in particular to the classification of knowledge. Thus, our aim isthreefold: to retrace the history of the so-called “universal” documentary classificationsand to highlight the specific contribution of French authors to the field of knowledgeorganization, in particular that of the Encyclopaedists of the Age of Enlightenment. Thishistoriographical approach is followed by a critical examination of classifications andtheir place in the digital age, and addressing the ethical issues of KOS.